2005
DOI: 10.1089/hum.2005.16.1318
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Block Copolymers Promote Gene Delivery In Vivo to Pathological Skeletal Muscles

Abstract: We reported that amphiphilic block copolymers hold promise as nonviral vectors for the delivery of plasmid DNA, ranging from 4.7 to 6.2 kb, to healthy muscle for the production of local or secreted proteins. To evaluate the efficiency of these vectors to deliver large plasmid DNA molecules to pathological muscles, plasmid DNAs of various lengths were complexed with Lutrol or poloxamine 304 and injected intramuscularly into dystrophic muscles. Lutrol-DNA and poloxamine 304-DNA complexes promoted gene transfer i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 11 publications
1
34
0
1
Order By: Relevance
“…Thereby we aimed to draw correlations between their physicochemical properties and their transfection efficiency, which is of crucial importance for the development of nonviral vectors. In our previous works, we have reported that mixing DNA with PE6400 block copolymer or Lutrol ® increased either reporter and therapeutic genes expression in skeletal or cardiac muscles and in lungs, including the corresponding pathological tissues such as Duchenne Muscular Distrophy muscles and cystic fibrosis lungs (10,12,13). Proofs of PEO-PPO-PEO-based formulations effectiveness have also been reported by Lemieux et al (8) who have used mixture of L61 and F127 to transfect muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby we aimed to draw correlations between their physicochemical properties and their transfection efficiency, which is of crucial importance for the development of nonviral vectors. In our previous works, we have reported that mixing DNA with PE6400 block copolymer or Lutrol ® increased either reporter and therapeutic genes expression in skeletal or cardiac muscles and in lungs, including the corresponding pathological tissues such as Duchenne Muscular Distrophy muscles and cystic fibrosis lungs (10,12,13). Proofs of PEO-PPO-PEO-based formulations effectiveness have also been reported by Lemieux et al (8) who have used mixture of L61 and F127 to transfect muscle.…”
Section: Discussionmentioning
confidence: 99%
“…These observations prompted researchers to explore and define new breakthrough approaches for in vivo gene transfer. In this context, others polymers displaying few or no charges have been recently developed and appear very promising to transfect efficiently and safely various organs in vivo after loco-regional administration in muscle and heart [52][53][54][55][56][57], lung [58] and eyes [59]. These block polymers consisting of poly(ethylene oxide) (PEO) and poly(propylene oxide) (PPO) exhibit amphiphilic properties in aqueous solutions, because PPO homopolymer phase-separates from water at relative low temperature, whereas POE is well soluble in water.…”
Section: New Classes Of Vectors Promote High Gene Transfer In Vivomentioning
confidence: 99%
“…Genmutationen, die zu einem Verlust des codierenden Proteins führen -jedoch nicht zu einem neuen toxischen Produkt -sind theoretisch einer Genersatztherapie zugänglich. Das zu ersetzende Gen kann hierfür mittels "nackter" DNA [37], DNA komplexiert mit kationischen Polymeren als Träger [38] oder mittels viraler Vektoren [39,40] in den Empfängerorganismus, im Speziellen in das Muskelgewebe, geschleust werden (• " Abb. 3).…”
Section: Klinische Studienunclassified